2018
DOI: 10.1097/ogx.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis on the Effect of Aspirin Use for Prevention of Preeclampsia on Placental Abruption and Antepartum Hemorrhage

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
1
17
0
2
Order By: Relevance
“…Whilst no reviews have assessed previously the effect of LDA on NICU admission, a recent secondary analysis from the 2017 ASPRE trial demonstrated a 70% reduction in the length of NICU stay for those babies whose mothers received LDA, compared to placebo, in pregnancy. Our finding of a non‐significant slight increase in the risk of placental abruption when LDA is started > 16 weeks is also consistent with a recent meta‐analysis. In addition, this study has provided further information regarding other important perinatal outcomes which not only supports the safety of LDA prophylaxis in pregnancy, but also raises the question of whether it should be used more widely to improve outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…Whilst no reviews have assessed previously the effect of LDA on NICU admission, a recent secondary analysis from the 2017 ASPRE trial demonstrated a 70% reduction in the length of NICU stay for those babies whose mothers received LDA, compared to placebo, in pregnancy. Our finding of a non‐significant slight increase in the risk of placental abruption when LDA is started > 16 weeks is also consistent with a recent meta‐analysis. In addition, this study has provided further information regarding other important perinatal outcomes which not only supports the safety of LDA prophylaxis in pregnancy, but also raises the question of whether it should be used more widely to improve outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, women who were exposed to low‐dose aspirin during pregnancy had similar mean blood loss to those who were not exposed to low‐dose aspirin . A recent meta‐analysis involving 12 585 pregnant women showed that the use of aspirin at less than 100 mg/d or greater than or equal to 100 mg/d, regardless of initiation time (≤16 or >16 weeks), was not associated with an increased risk of placental abruption or prepartum hemorrhage . In the ASPRE trial, women exposed to aspirin did not have increased risk of bleeding adverse events .…”
Section: First Trimester Prevention Of Preterm Pre‐eclampsiamentioning
confidence: 99%
“…Randomized trials on the use of aspirin have reported that the drug is not associated with increased risk of adverse events and, in the case of abruption or antepartum hemorrhage, the risk may actually be reduced. In this respect, it may be acceptable that, in screening for PE, the SPR could be about 15% or even higher so as to maximize the DR.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analyses of the ASPRE trial demonstrated that, first, the beneficial effect of aspirin depends on compliance and the reduction in incidence of preterm PE may be about 75% in those with compliance of ≥ 90%, second, there is no heterogeneity in the aspirin effect in subgroups defined according to maternal characteristics, obstetric history and history of pre‐existing medical conditions, except for chronic hypertension, for which aspirin may not be useful in the prevention of PE, and, third, use of aspirin reduces the length of stay in the neonatal intensive care unit by about 70%, mainly due to a decrease in the rate of birth at < 32 weeks' gestation because of prevention of early PE. Recent meta‐analyses reported that aspirin reduces the risk of preterm PE by 67%, provided that the daily dose of the drug is ≥ 100 mg and gestational age at onset of therapy is ≤ 16 weeks, and that aspirin at a dose of ≥ 100 mg initiated at ≤ 16 weeks, rather than > 16 weeks, may decrease the risk of placental abruption or antepartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%